PENGARUH QUICK RATIO DAN TOTAL ASSET TURNOVER TERHADAP NET PROFIT MARGIN PADA PT SOLUSI BANGUN INDONESIA Tbk PERIODE 2013-2023 - Sri Marlinah; Sairin (Journal of Research and Publication Innovation, 2025)
This research aims to find out how the impact of Quick Ratio and Total Asset Turnover on Net Profit Margin at PT Solusi Bangun Indonesia Tbk both partially and simultaneously. This study uses a quantitative descriptive method with data obtained from the Financial Statements of PT Solusi Bangun Indonesia Tbk from the official website of PT Solusi Bangun Indonesia Tbk from 2013 to 2023. All tests conducted using the operation of the SPSS version 26 application.Quick Ratio varable test results have effect on Net Profit Margin with T test partially with tcount > ttable is 4,321 > 2,3060 and significant value is 0,003 < 0,05. Total Asset Turnover variable have effect on Net Profit Margin with tcount > ttable is 3,608 > 2, 3060 and significant value is 0,007 < 0,05. Quick Ratio and Total Asset Turnover against Net Profit Margin with known F test, Fcount is greater than Ftable is 14,715 > 4,256 and signifying value is 0.002 < 0.05. So the explanation that the variable that Quick Ratio and Total Asset Turnover significantly influence simultaneously on Net Profit Margin with a coefficient of determination of 73.3% and the remaining 26.7% is influenced by other variables not tested in this study.